2022
DOI: 10.1142/s0219455422400107
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation for Vortex-Induced Vibration (VIV) of a High-Rise Building Based on Two-Way Coupled Fluid-Structure Interaction Method

Abstract: The vortex shedding phenomenon caused by flow separation at windward corners of a high-rise building would lead to significant vortex-induced vibrations (VIVs). This paper proposes a novel and efficient two-way coupled fluid-structure interaction (FSI) method named as equivalent lumped mass system (ELMS) method to study the wind-induced responses of the Common Advisory Aeronautical Council (CAARC) building. The numerical results of ELMS are validated based on available data of aeroelastic tests. To verify the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Péntek [13] considered the additional mass damper's influence on structural wind-induced displacement using an FSI method. Yan [14] proposed an efficient two-way FSI technique based on an equivalent concentrated mass system. By comparing with other FSI equivalent methods and aerodynamic elasticity test data, it was found that this method, combined with LES, can efficiently capture and simulate the vortex-induced resonance phenomenon of CAARC high-rise buildings.…”
Section: Introductionmentioning
confidence: 99%
“…Péntek [13] considered the additional mass damper's influence on structural wind-induced displacement using an FSI method. Yan [14] proposed an efficient two-way FSI technique based on an equivalent concentrated mass system. By comparing with other FSI equivalent methods and aerodynamic elasticity test data, it was found that this method, combined with LES, can efficiently capture and simulate the vortex-induced resonance phenomenon of CAARC high-rise buildings.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of computing technology, many scholars have investigated wind-induced vibration by using fluid-structure interaction simulations [3,25,26]. Fluid-structure interaction wind vibration simulations typically encompass one-way fluid-structure interaction [27][28][29] and two-way fluid-structure interaction [30][31][32]. In one-way FSI studies on wind-induced vibration in high-rise buildings, wind load data are typically acquired through numerical calculations or experiments, and subsequently applied to the structural finite element model [29].…”
Section: Introductionmentioning
confidence: 99%